2013
DOI: 10.1242/dmm.011734
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel extracorporeal bowel model to study luminal approaches to treat inflammatory bowel disease

Abstract: SUMMARYWe have established an extracorporeal bowel model system for the analysis of early events in inflammatory bowel disease (IBD) and therapeutic applications. This model consists of an intestinal segment that is cannulated and perfused in situ, allowing the investigation of cellular responses of apical mucosa cells on luminal applied substances. Short-term treatment with iodoacetamide mimicked experimental intestinal inflammation in IBD, as indicated by histological alterations such as hemorrhage, hyperemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…However, it failed to prevent shortening of the colon. These data correspond with the findings in our previous studies, where the application of a diosmectite also decreased histological alteration and improved the overall histological score [13]. Another animal study from González et al, which used a TNBS colitis model in rats, showed that the diosmectite treatment resulted in amelioration of the intestinal morphological signs and reduced the severity of diarrhea [11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it failed to prevent shortening of the colon. These data correspond with the findings in our previous studies, where the application of a diosmectite also decreased histological alteration and improved the overall histological score [13]. Another animal study from González et al, which used a TNBS colitis model in rats, showed that the diosmectite treatment resulted in amelioration of the intestinal morphological signs and reduced the severity of diarrhea [11].…”
Section: Discussionsupporting
confidence: 90%
“…We found positive effects on the clinical symptoms associated with DSS-colitis, such as weight loss, stool consistency and occult blood. Furthermore, the positive impact of diosmectite on the histological score, as observed in a previous in vivo study, could be confirmed [13]. Analysis of the gut microbiota composition identified a possible microbiome shaping potential.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, the TLR4/NF-κB signaling pathway was activated in both the H7 and H14 mice. Breitruck et al [59] reported that the intestinal mucosal structure is damaged in mice with IBD. This injury is characterized by severe bleeding and IL-6 and IL-10 upregulation.…”
Section: Discussionmentioning
confidence: 99%